Myeloid Neoplasms Following Solid Organ Transplantation: Clinicopathologic Studies of 23 Cases. Issue 1 (7th December 2017) - Wu, Bin; Ingersoll, Kimberly; Jug, Rachel; Yang, Lian-he; Luedke, Catherine; Lo, Amanda; Su, Pu; Liu, Xin; Rehder, Catherine; Gong, Jerald; Lu, Chuanyi Mark; Wang, Endi
Abstract: Objectives: Myeloid neoplasms (MNs) after solid organ transplant are rare, and their clinicopathologic features have not been well characterized. Methods: We retrospectively analyzed 23 such cases. Results: The ages ranged from 2 to 76 years, with a median of 59 years at the diagnosis. The median interval between the transplant and diagnosis was 56 months (range, 8-384 months). The transplanted organs included liver in five, kidney in six, lung in five, heart in six, and heart/lung in one case(s). The types of MN included acute myeloid leukemia (AML) in 12, myelodysplastic syndrome (MDS) in five, chronic myelogenous leukemia (CML) in four, and myeloproliferative neoplasms (MPNs) in two cases. Cytogenetics demonstrated clonal abnormalities in 18 (78.3%) cases, including unbalanced changes in 10 (55.6%), Philadelphia chromosome in four (22.2%), and other balanced aberrations in four (22.2%) cases. Thirteen (56.5%) patients died, with an estimated median survival of 9 months. With disease stratification, AML and MDS have short median survivals (3.5 and 7 months, respectively), with an initial precipitous decline of the survival curve. Conclusions: Posttransplant MNs have a latency period between that seen in AML/MDS related to alkylators and that associated with topoisomerase II inhibitors. The cytogenetic profile suggests a mutagenic effect on leukemogenesis. The clinical outcome for AML/MDS is dismal, with death occurring at an early phase of treatment.